2013
DOI: 10.1111/jzs.12026
|View full text |Cite
|
Sign up to set email alerts
|

Species distribution, ecology, abundance, body size and phylogeny originate interrelated rarity patterns at regional scale

Abstract: The most pervasive macroecological patterns concern (1) the frequency distribution of range size, (2) the relationship between range size and species abundance and (3) the effect of body size on range size. We investigated these patterns at a regional scale using the tenebrionid beetles of Latium (Central Italy). For this, we calculated geographical range size (no. of 10-km square cells), ecological tolerance (no. of phytoclimatic units) and abundance (no. of sampled individuals) using a large database contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…It is possible, for example, that large insect species are more widely distributed (Hoffsten, 2004;Fattorini et al, 2013) because they are stronger active fliers than small species (Hoffsten, 2004;Heino, 2013), and they should thus show more uniform OFDs than small species. Small species should be a more species-rich group than that of larger species (Hutchinson & MacArthur, 1959), and the probability of finding more rare species should thus increase with decreasing body size and lead to pronounced satellite mode in OFDs.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible, for example, that large insect species are more widely distributed (Hoffsten, 2004;Fattorini et al, 2013) because they are stronger active fliers than small species (Hoffsten, 2004;Heino, 2013), and they should thus show more uniform OFDs than small species. Small species should be a more species-rich group than that of larger species (Hutchinson & MacArthur, 1959), and the probability of finding more rare species should thus increase with decreasing body size and lead to pronounced satellite mode in OFDs.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, range size and body size relationships are some of the most consistent macroecological patterns across a variety of taxa (Brown, ; Lawton, , ; Gaston & Blackburn, ). Range size increases with body size in birds (Brown & Maurer, ), mammals (Brown & Maurer, ), beetles (Fattorini et al ., ), marine fish (Strona et al ., ) and freshwater fish (Pyron, ; Rosenfield, ; Bertuzzo et al ., ) with few exceptions (Gaston & Blackburn, ; Blanchet et al ., ). Larger species have greater ranges, primarily due to increased energy demands (Brown & Maurer, ) and dispersal capacity (Jenkins et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Such studies have often attempted to link life‐history traits to species decline (e.g. Davies et al ., ; Fattorini et al ., ). Most have found that interactions among multiple traits were most useful for predicting which species are more at risk of extinction (Davies et al ., ; Henle et al ., ; Driscoll & Weir, ; Fattorini et al ., ).…”
Section: Beetle Traits As Tools For Understanding Community Patternsmentioning
confidence: 97%
“…Davies et al ., ; Fattorini et al ., ). Most have found that interactions among multiple traits were most useful for predicting which species are more at risk of extinction (Davies et al ., ; Henle et al ., ; Driscoll & Weir, ; Fattorini et al ., ). For example, species abundance combined with habitat selection (specialists/generalists) explains some species' sensitivity to decline (Davies et al ., ).…”
Section: Beetle Traits As Tools For Understanding Community Patternsmentioning
confidence: 97%